Testicular Seminoma Presenting as Gastrointestinal Bleeding: A Rare Cause of Metastatic Disease in the Stomach - Maria Azevedo Silva; Carina Leal; André Ruge; Alexandra Fernandes; Maria Fernanda Cunha; Helena Vasconcelos (GE: Portuguese Journal of Gastroenterology, 2022)
Introduction: Gastric metastases are quite infrequent. When arising from testicular germ cell tumors, gastric metastases are usually associated with nonseminomas. Case Report: A 45-year-old man presented with upper gastrointestinal bleeding, severe anemia, and elevated lactate dehydrogenase. Endoscopy revealed three atypical-looking gastric ulcers. Abdominal computed tomography showed an extensive heterogeneous retroperitoneal mass and a smaller one in the pelvis. Biopsies of both the ulcers and the retroperitoneal mass revealed a highly proliferative neoplasia of unknown origin. While the diagnostic work up was taking place, the patient complained of a testicular mass which was resected, after suspicious findings in the ultrasound. Histopathologic findings revealed a testicular seminoma. Revision of previous biopsies was compatible with metastatic seminoma to the stomach and the retroperitoneum. Discussion/Conclusion: Gastric metastasis arising from testicular seminoma is quite infrequent and usually diagnosed after the primary tumor is known. We report a rare case of a testicular seminoma presenting as upper gastrointestinal bleeding due to gastric metastases. This case highlights the importance of detailed anamnesis and physical examination in the differential diagnosis of atypical gastric ulcers with initial inconclusive work up and emphasizes an unusual manifestation of a germ cell malignancy.